POLA KONSUMSI, STATUS GIZI DAN PRESTASI BELAJAR PADA ANAK VEGETARIAN DAN NON VEGETARIAN KELAS V SEKOLAH DASAR DI YAYASAN PERGURUAN BODHICITTA MEDAN TAHUN 2013 - roy charles marpaung; Albiner Siagian; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Having consumption in vegetarian pattern is defined taking consumption pattern of meal and food resources of vegetable only. Accordingly, a kid having less protein energy is going to get retardation in growth, susceptible on illness, noted mainly resulted in poorly condition in intelligence. The objective of this study is to determine the differences of the consumption pattern, nutrition status and study performance of kids with vegetarian and non vegetarian at Yayasan Perguruan Buddhis Bodhicitta-Institute of Medan for 2014. This study adopted a descriptive survey method with cross sectional approach. The research dealt with the condition differenced in consumption pattern, nutrition status and performance in study of those kids with vegetarian and non-vegetarian, provided them questionnaire involved 86 respondents that took them all in simple randomly. The result of study indicated that those kids in vegetarian in totally 52 kids (60.4%) and non-vegetarian of total 34 kids (39.6%). The distribution of age as respondent mostly noted in 11 years old about 37 kids (43.0%), the education rate of parent of respondent noted mostly having graduated SMA namely 30 kids (34.9%), their profession as parent of kid noted in private noted 50 people (58.1%), their consumption rate in energy noted in category of moderate namely about 32 kids (37.2%), consumption rate in protein noted of category moderate about 31 kids ((36.0%). TB/U of respondent mostly noted is category in normal of 48 kids (55.85), IMT of respondent mostly noted is category in normal of 23 kids (26.7%). Their performance as respondent mostly noted in category of less some 50 kids (58.1%). It is suggestible to those parent of kid in their daily life got consumption pattern of vegetarian could taken their food for meal in vegetarian with highly protein, calcium, and contained sufficiently zinc so that the nutrition required for growth should be fulfilled and the kids got as required. Keywords : consumption pattern, nutrition status, study performance, vegetarian.